If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5(5x + 18) = 22 Reorder the terms: -3x + -5(18 + 5x) = 22 -3x + (18 * -5 + 5x * -5) = 22 -3x + (-90 + -25x) = 22 Reorder the terms: -90 + -3x + -25x = 22 Combine like terms: -3x + -25x = -28x -90 + -28x = 22 Solving -90 + -28x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 90 + -28x = 22 + 90 Combine like terms: -90 + 90 = 0 0 + -28x = 22 + 90 -28x = 22 + 90 Combine like terms: 22 + 90 = 112 -28x = 112 Divide each side by '-28'. x = -4 Simplifying x = -4
| -54=-1.5+h | | -54=1.5+h | | 8x-89=5x-11 | | 42y+6=6(2y+1) | | 148-7x=20x+16 | | 23x-8=14x+7 | | 2v^3+5v^2-14v-35=0 | | 2/3=-3/5 | | 2.4x+7=31-0.6x | | 6=-3/5 | | 5a+15-a=31 | | -2c+4=-8 | | X^4=12x^2+8x^3 | | -x=0.61 | | 5/6=10 | | 5d+2(2d+3)=42 | | 7(3n-4)=(2n+9)+3 | | -3x-5(7x+17)=-9 | | 53+x+27=180 | | 2m-3m=n+12 | | 11x=8x-12 | | 12r-7r=3 | | 12w^2-9w=0 | | 6(x-11)-4x=-72 | | 181-4x=23x+22 | | (b-3)(3b-1)-2b(b+2)= | | -3p+2=1 | | 2x-54490=292400 | | 3(5-x)+6=0 | | y+-0.3= | | 9a+5=3 | | 13-9x=16-16x |